Gender equality in academic publishing: action from the BJPsych. - Upthegrove, R; de Cates, A; Shuttleworth, A; Tracy, DK; Broome, MR; Lingford-Hughes, A (Cambridge University Press, 2020)
Women in academic publishing and academic psychiatry face many challenges of gender inequality, including significant pay differentials, poor visibility in senior positions and a male-dominated hierarchical system. We discuss this problem and outline how the BJPsych plans to tackle these issues it in its own publishing.